NETWORKING AND MONETIZATION STRATEGIES OF SPANISH-SPEAKING FINFLUENCERS: A CO-LINK ANALYSIS OF YOUTUBE DESCRIPTIONS - Tomasena, José M.; Arredondo, Diego; López-González, Hibai (AoIR Selected Papers of Internet Research, 2026)
This study examines the networking and monetization strategies employed by Spanish-speaking financial influencers (finfluencers) on YouTube. Given the precarious labor market conditions facing young people, finfluencers promise easy and fast ways to “get rich”. These alternative pathways to financial success include cryptocurrencies, trading, online gambling, and internet-based business, like microtasking, dropshipping or online mentoring. Through a co-link analysis of video descriptions obtained through YouTube API v3 (n=68,455), this research identifies key monetization methods, including course sales, affiliate marketing, crowdfunding, and direct product sales. Additionally, BERTopic modeling reveal dominant thematic trends within finfluencer content. Preliminary findings indicate a strong commercial orientation, with content often framed as “financial education” that includes links to affiliate marketing or course sales, a deliberate strategy to diversity their online presence in other platforms like TikTok, Instagram or Spotify, and topics related to trading, gaining money from home, Paypal and cryptocurrencies. This study contributes to the underlying business models of finfluencers in order to assess their potential impact on audiences and their role in shaping consumer behavior.